THE ROLE OF EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE IN THE IMPACT OF EMPLOYEE DEVELOPMENT AND EMPLOYEE COMMUNICATION ON EMPLOYEE PERFORMANCE AT BANK INDONESIA LHOKSEUMAWE AND BANDA ACEH - Endra Eka Putra; Hadi Arifin; Mariyudi (CV. Radja Publika, 2024)
This study aims to examine the influence of Employee Development and Employee Communication on Employee Performance through Employee Engagement as an intervening variable at Bank Indonesia Lhokseumawe and Banda Aceh. The data for this study consists of 103 employees who responded to a questionnaire distributed via Google Forms. The data analysis tool used is PLS-SEM, which is operated with the SmartPLS program. The results of the study found that Employee Development and Employee Communication have a significant impact on Employee Engagement and Employee Performance. Employee Engagement also significantly enhances Employee Performance. In testing the mediation effect, Employee Engagement can partially mediate the relationship between the independent and dependent variables. The findings of this study are expected to contribute to stakeholders' formulation of employee development strategies as an essential resource for every organization.